2011
DOI: 10.1086/659655
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Performance Pay: Experimental Evidence from India

Abstract: Performance pay for teachers is frequently suggested as a way of improving education outcomes in schools, but the theoretical predictions regarding its effectiveness are ambiguous and the empirical evidence to date is limited and mixed. We present results from a randomized evaluation of a teacher incentive program implemented across a large representative sample of government-run rural primary schools in the Indian state of Andhra Pradesh. The program provided bonus payments to teachers based on the average im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
281
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(295 citation statements)
references
References 64 publications
12
281
0
2
Order By: Relevance
“…To eliminate confounding influences from school visits paid only to the treatment group during the CAL sessions, as Muralidharan and Sundararaman (2011) did in their RCT on teacher performance pay, every time our volunteers visited Source: Authors' survey. * * Significant at 5%.…”
Section: Cal Control Group (The Control Group In the Core Sample)mentioning
confidence: 99%
“…To eliminate confounding influences from school visits paid only to the treatment group during the CAL sessions, as Muralidharan and Sundararaman (2011) did in their RCT on teacher performance pay, every time our volunteers visited Source: Authors' survey. * * Significant at 5%.…”
Section: Cal Control Group (The Control Group In the Core Sample)mentioning
confidence: 99%
“…Nonetheless, two important experiments offer insights that suggest that incentives can be highly effective and far cheaper to implement in developing countries. A randomized controlled trial conducted in the state of Andhra Pradesh in India assigned teachers to one of three groups: no incentive; a school-wide incentive; or an individual incentive [11]. As a percentage of teacher salaries, the incentives were substantial, but in absolute terms they were inexpensive-typically less than US $100 per teacher.…”
Section: International Evidence On Teacher Financial Incentivesmentioning
confidence: 99%
“…It should be noted, however, that details on costs are only reported in 13 out of the 29 studies that form the basis of the systematic review. A list of these 13 studies and the reported costs associated with the interventions they document can be found in Table B. 2 Muralidharan and Sundararaman (2011) and Muralidharan (2012) group-based bonus payments to teachers based on improvement in students' test scores USD 2 per child per year Muralidharan and Sundararaman (2011) and Muralidharan (2012) individual-based bonus payments to teachers based on improvement in students' test scores USD 3 per child per year Muralidharan and Sundararaman (2013a) school choice program featuring lottery-based allocation of school vouchers savings of 102 USD per child per year Muralidharan and Sundararaman (2013b) extra contract teachers USD 6 per child per 24 months A first strand of research investigates the roles of interventions targeting individuals on the supplyside of the education sector, i.e. teachers.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…There was no evidence that teacher bonus payments had any adverse consequences (like more of teachers' efforts being channeled towards incentivized subjects as opposed to non-incentivized ones such as science and social studies). In fact, incentive schools performed significantly better than those in a separate group of randomly chosen schools that had received additional schooling inputs of similar value (Muralidharan and Sundararaman, 2011;Muralidharan, 2012).…”
mentioning
confidence: 90%
See 1 more Smart Citation